Near infrared planar tumor imaging and quantification using nanosized Alexa 750-labeled phospholipid micelles - Aristarchos Papagiannaros (Dove Medical Press, 2009)
Aristarchos Papagiannaros, Amit Kale, Tatyana S Levchenko, Dmitry Mongayt, William C Hartner, Vladimir P TorchilinDepartment of Pharmaceutical Sciences and Center for Pharmaceutical Biotechnology and Nanomedicine, Northeastern University, Boston, MA, USAAbstract: A novel highly biocompatible near infrared nanosized contrast agent was developed and used for rapid tumor detection and quantification using planar optical imaging and analysis. With this in mind, the near infrared fluorescent dye Alexa 750 was covalently attached to polyethylene glycol-phosphatidylethanolamine (PEG-PE) conjugate, and double labeled (with Alexa and rhodamine) PEG-PE micelles were injected into mice and observed using planar optical imaging. Pixel intensity data from the tumor site were normalized versus the autofluorescence of the animal at the same time point and normalized as signal to noise over the scattered light from the various tissues of the mice. The detected signal from the tumor was higher than the background noise allowing for rapid detection of the tumor. The tumor was clearly visible within one hour. Some signal was also detected from the abdomen of the mice. As determined by microscopy analysis, other organs of accumulation were the liver and kidney, which corresponded well to the data from the whole body imaging animal studies.Keywords: nanotechnology, nanomedicine, cancer imaging agents, near infrared imaging, micelles